2014
DOI: 10.2528/pierc14052203
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Dual Sharp Band-Notched Uwb Antenna With Open-Ended Slots

Abstract: Abstract-A compact microstrip-fed antenna with dual band-notched characteristics for ultrawideband (UWB) applications is presented.By introducing two open-ended inverted L-shaped slots, two sharp notches are achieved at frequencies of 3.16-3.70 GHz and 5.10-5.95 GHz for VSWR > 2. A rectangular slot in the ground plane can improve the impedance bandwidth of the proposed antenna. The prototype occupies a compact area of 22 × 26 mm 2 . The measurement results indicate that the proposed antenna can reject the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…With further study and optimization of dual band microstrip antenna [2] it has been found that the return loss for dual band frequency at 2.4GHz is -43dB and at 3GHz is -27dB. To get compact size and maintaining optimum performance of antenna for multiple bands i.e., dual band, triple band antennas etc., various shapes of antenna was integrated [3]. As suggested in [4], introducing slot into patch (L-Shape) increases the impedance bandwidth up to 13%.…”
Section: Introductionmentioning
confidence: 99%
“…With further study and optimization of dual band microstrip antenna [2] it has been found that the return loss for dual band frequency at 2.4GHz is -43dB and at 3GHz is -27dB. To get compact size and maintaining optimum performance of antenna for multiple bands i.e., dual band, triple band antennas etc., various shapes of antenna was integrated [3]. As suggested in [4], introducing slot into patch (L-Shape) increases the impedance bandwidth up to 13%.…”
Section: Introductionmentioning
confidence: 99%